The Effect of Internship Experience on Work Readiness among Hospitality Management Students at Universitas Negeri Padang - Yanza, Nauval Afif; Ferdian, Feri (LITPAM, 2026)
This study examines the association between internship experience and work readiness among students of the D-IV Hospitality Management Study Program at Universitas Negeri Padang, class of 2022. Although prior studies have generally confirmed that internships improve employability and career readiness, limited empirical evidence explains this relationship in a vocational hospitality program where students report very high readiness but only a small proportion enter work immediately after internship completion. Using a quantitative descriptive and associative survey design, this study involved 100 students selected from a population of 132 internship participants through simple random sampling based on the Slovin formula with a 5% margin of error. Data were collected using a structured five-point Likert questionnaire consisting of 15 internship-experience items and 12 work-readiness items. Internship experience was measured through work knowledge, work skills, adaptive attitude, work attitude, and understanding of the work environment, while work readiness was measured through skills, knowledge, understanding, and personality attributes. Instrument testing showed that all items were valid, with Cronbach’s alpha values of 0.948 for internship experience and 0.956 for work readiness. Descriptive results indicated that internship experience was very good (M = 4.4393) and work readiness was also very good (M = 4.3033). Simple linear regression using total variable scores showed that internship experience significantly predicted work readiness (B = 0.645, t = 8.643, F = 74.699, p < 0.001, R2 = 0.433). The findings imply that structured, relevant, and supervised internship programs are important for strengthening students’ workplace knowledge, technical and communication skills, professional adaptation, and confidence, but work readiness should also be supported through career preparation, mentor quality, curriculum alignment, and post-internship transition strategies.